2020
DOI: 10.2298/jmmb190219003w
|View full text |Cite
|
Sign up to set email alerts
|

Volatilization characteristics of high-lead slag and its influence on measurement of physicochemical properties at high temperature

Abstract: Volatilization causes measurement deviations of physicochemical properties for volatiles-containing slag at high temperature. Hence, investigating the degree of volatilization and identifying the volatilization mechanism and deviation rules are crucial to improve the accuracy of the measured properties. Here, PbO-FeOx-CaO-SiO2-ZnO slag system was selected as a research subject. The volatile characteristics and non-isothermal intrinsic kinetic models of high-temperature volatilization for lead slag were establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Our group measured the weight loss of PbO slag with TG-DSC. It is detected that the weight loss (i.e., evaporation) to slag with initial PbO content (determined in slag sample preparing) of 21.54 % and 43.09 % can reach to 21.62 % and 38.69 %, respectively, at temperature between 736 °C to 1450 °C [17]. Thus, in the physicochemical property measurement of slag at high temperature, the evaporation is absolutely not neglectable.…”
Section: Prefacementioning
confidence: 99%
See 2 more Smart Citations
“…Our group measured the weight loss of PbO slag with TG-DSC. It is detected that the weight loss (i.e., evaporation) to slag with initial PbO content (determined in slag sample preparing) of 21.54 % and 43.09 % can reach to 21.62 % and 38.69 %, respectively, at temperature between 736 °C to 1450 °C [17]. Thus, in the physicochemical property measurement of slag at high temperature, the evaporation is absolutely not neglectable.…”
Section: Prefacementioning
confidence: 99%
“…Thus, in the physicochemical property measurement of slag at high temperature, the evaporation is absolutely not neglectable. The traditional slag property measurement method in not fit these slags again [5,6,17]. Then how much the evaporation effect is?…”
Section: Prefacementioning
confidence: 99%
See 1 more Smart Citation
“…For example, the oxygen potential not only affects the existence of volatiles but also affects the activation energy of volatilisation reactions [4], which may lead to nonlinear variations in the rate of volatilisation reactions. Moreover, the contents and diffusion conditions of volatiles also significantly impact the volatilisation rate [10]. In physical property tests, including slag melting temperature and viscosity tests, continuous volatilisation will change the composition and properties of the slag, thereby adversely affecting the test results.…”
Section: Introductionmentioning
confidence: 99%
“…However, as an intermediate product of volatilisation reactions, the proportion of PbO has a great effect on the total volatilisation. Yaru Cui et al [10] investigated the volatilisation characteristics of high-lead slag during physical property tests. Their study revealed that when the temperature exceeded 900 • C, the volatilisation proportion of PbO(s) exceeded 50%, and diffusion conditions were the main influencing factor.…”
Section: Introductionmentioning
confidence: 99%